1996
DOI: 10.1163/156853896x00270
|View full text |Cite
|
Sign up to set email alerts
|

The effects of insulin on TSH secretion and the morphology and physiology of the thyroid in the lizard Podarcis s. sicula

Abstract: Insulin was administered to Podarcis sicula in winter, when the thyroid gland is inhibited. The activity of the thyroid increased, plasma concentrations of thyroid hormones and hepatic 5'-monodeiodinase activity (MDA) increased, and thyroid stimulating hormone (TSH) concentrations fell to undetectable values. This result confirms the influence of insulin on the activity of the thyroid gland in the lizard species studied. The mechanisms are still unclear, although there is evidence which leads us to believe tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Conversely, the abrupt increase in thyroid-hormone plasma levels suggests a direct action of VIP on the thyroid gland. In our previous studies, it was demonstrated that thyroid gland stimulation in P. sicula may be independent of interference at pituitary' level (Laforgia et al, 1996;Sciarrillo et al, 1999). These results are in agreement with the hypothesis described in a recent paper (Sciarrillo et al, 2000) about regulation of the pituitary-thyroid axis.…”
Section: Discussionmentioning
confidence: 94%
“…Conversely, the abrupt increase in thyroid-hormone plasma levels suggests a direct action of VIP on the thyroid gland. In our previous studies, it was demonstrated that thyroid gland stimulation in P. sicula may be independent of interference at pituitary' level (Laforgia et al, 1996;Sciarrillo et al, 1999). These results are in agreement with the hypothesis described in a recent paper (Sciarrillo et al, 2000) about regulation of the pituitary-thyroid axis.…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study (Laforgia et al, 1996), it was examined the effects of insulin treatment on the thyroid of the same lizard, resulting in an activation of thyroid metabolism. In fact, insulin treatment caused numerous changes in the thyroid gland which can be summarized as follows: 0) increase in plasma T4 and T3 levels; (ii) unchanged plasma TSH levels; increased hepatic T3 and T4 contents and 5'-T4ORDII-monodeiodinase activity; (iii) tall epithelial cells and colloid in reabsorption in thyroid follicles.…”
Section: Discussionmentioning
confidence: 99%